2014
DOI: 10.1177/0300985814529312
|View full text |Cite
|
Sign up to set email alerts
|

Survivin and Related Proteins in Canine Mammary Tumors

Abstract: Survivin is reexpressed in most human breast cancers, where its expression has been associated with tumor aggressiveness, poor prognosis, and poor response to therapy. Survivin expression was evaluated in 41 malignant canine mammary tumors (CMTs) by immunohistochemistry, in relation to histological grade and stage, and correlated with that of some related molecules (b-catenin, caspase 3, heat shock proteins) to understand their possible role in canine mammary tumorigenesis. An increase in nuclear survivin expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 27 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Survivin is encoded on chromosome 17q25 and is a 142-amino acid protein with a unique BIR domain. Survivin expression is low in normal adult tissue, with the exception of the thymus and embryonic organization (Gho et al, 2011), but is strongly expressed in several types of human cancer, including colon carcinoma (Hasan et al, 2014), breast carcinoma (Bongiovanni et al, 2014), and urothelial carcinoma (Chen et al, 2014). In this study, western blotting and real-time PCR analysis of fresh tissue showed significantly increased survivin expression in cancer versus chronic cervicitis, consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…Survivin is encoded on chromosome 17q25 and is a 142-amino acid protein with a unique BIR domain. Survivin expression is low in normal adult tissue, with the exception of the thymus and embryonic organization (Gho et al, 2011), but is strongly expressed in several types of human cancer, including colon carcinoma (Hasan et al, 2014), breast carcinoma (Bongiovanni et al, 2014), and urothelial carcinoma (Chen et al, 2014). In this study, western blotting and real-time PCR analysis of fresh tissue showed significantly increased survivin expression in cancer versus chronic cervicitis, consistent with previous findings.…”
Section: Discussionsupporting
confidence: 90%
“…However, in veterinary medicine only few data have been published about the implication of apoptosis in the diagnosis and/or malignancy of canine tumours and, to the best of our knowledge, there is only a single study that used an antibody to the active form of caspase-3 in these tumours (Bongiovanni et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In the selected areas a total of 1000 tumour cells were counted with the help of a microscopic grid, at high magnification. The results were expressed as a percentage of labelled cells in a total of 1000 tumour cells (Pathmanathan and Balleine, 2013;Bongiovanni et al, 2014).…”
Section: Quantification Of Immunoreactivitymentioning
confidence: 99%
See 2 more Smart Citations